Terapi aktivasi perilaku untuk mengurangi perilaku menarik diri pada pasien skizofrenia - Aisyah Putri Rawe Mahardika (Universitas Muhammadiyah Malang, 2021)
Subject in the this study experienced withdrawn behavior that is one of the negative symptoms of schizophrenia. Withdrawing is characterized by decrease in initiative behavior that can create functional impairments in life, work, relationships, social function, and self-care. The intervention used to reduce withdrawn behavior was Behavior Activation Therapy which arranged for nine sessions. The purpose of intervention was to increase daily activities by scheduling activities with monitoring. The results of the intervention showed an increase in the daily activities of the subjects. Subject begins to be able to carry out activities such as bathing, eating, taking regular medication, and cleaning the house. The success of interventions is also supported by family involvement in monitoring the activities and providing support to carry out the intervention well.